PEMBINAAN MORAL REMAJA PUTUS SEKOLAH PADA PSBR BUDI SATRIA PROVINSI KALIMANTAN SELATAN - Rusmaniah Rusmaniah (JURNAL SOCIUS, 2017)
Trackling the problem and children drop out of school is the responsibility of the state and public. One of the solution is through Bina Remaja Sosial Institution Budi Satria South Kalimantan Province.To accusedof coaching froam Bina Remaja Sosial Institution Budi Satria South Kalimantan Province, researchers focused matter as the following. (1) factors teenagers dropping out of school (2) the implementation guidance moral (3) by factors in support and factors barrier for developing moral. This research designed with descriptive qualitative design and using a list of queations as instrument interview in data collection. Based on the result of this research found that (1) tha process of servise training at Bina Remaja Sosial Institution Budi Satria South Kalimantan Province namely planning stages, the approach of early stage, stage services for panti, stage of the distribution, guidance advanced stage, termination. (2) the factors causing the teenager drop out of school namely economic factors, drop out , and family that lacking a harmonious.(3) by factors in support the implementation of the guidance among other people around, learning environment conducive, funding from the regional government, cooperation with outside , and cooperation among employees. (4) factors obstacles in the implementation of the guidance among other habits ugly beneficiaries who carried away into an environment panti, the son of princess promiscuity, background beneficiares different, a lack of facilities and infrastructure, and lack of the number of instructors. Keywords:Guidance, social institution, teenager, dropping out of school.Melacak masalah dan anak putus sekolah adalah tanggung jawab negara dan masyarakat. Satu solusinya adalah melalui Lembaga Bina Remaja Sosial Budi Satria Provinsi Kalimantan Selatan. Untuk dituduh melakukan pembinaan, Bina Remaja Sosial Institution Budi Satria Provinsi Kalimantan Selatan, peneliti memfokuskan perhatian sebagai berikut. (1) faktor remaja putus sekolah (2) pedoman pelaksanaan moral (3) oleh faktor pendukung dan faktor penghalang untuk pengembangan moral. Penelitian ini dirancang dengan rancangan deskriptif kualitatif dan menggunakan daftar antri sebagai instrumen wawancara dalam pengumpulan data.Berdasarkan hasil penelitian ini ditemukan bahwa (1) prosesi pelatihan servis di Bina Remaja Sosial Budi Satria Propinsi Kalimantan Selatan yaitu tahap perencanaan, pendekatan tahap awal, pelayanan panggung untuk panti, tahap pendistribusian, panduan stadium lanjut. , Penghentian (2) faktor penyebab remaja putus sekolah yaitu faktor ekonomi, putus sekolah, dan keluarga yang kurang harmonis. (3) Faktor pendukung dalam mendukung pelaksanaan bimbingan antara orang lain disekitarnya, belajar lingkungan kondusif, dana dari Pemerintah daerah, kerjasama dengan pihak luar, dan kerjasama antar karyawan. (4) faktor hambatan dalam pelaksanaan pembinaan antara lain kebiasaan penerima manfaat jelek yang terbawa ke lingkungan panti, anak pergaulan putri, latar belakang berbeda, kekurangan sarana dan prasarana, dan minimnya jumlah instruktur.Kata kunci: Bimbingan, lembaga sosial, remaja, putus sekolah.